Carbenoid Etherifications Catalyzed by “Green” Silver Nanoparticles and Iron-Copper Nanoparticles - A. Garcia, Marco; Garcia-Munoz, Angel; A. Pena, Josue; Trujillo-Reyes, Jessica; A. Morales-Luckie, Raul; Avalos-Borja, Miguel; R. Vilchis-Nestor, Alfredo; Sanchez-Mendieta, Victor; Corona, David; Cuevas-Yanez, Erick (Letters in Organic Chemistry, 2012)
Etherfication products were obtained from sodium salts of p-toluenesulfonylhydrazones in alcohol solutions at reflux temperature on treatment with catalytic amounts of iron-copper nanoparticles, and silver nanoparticles, which were prepared from Camellia sinensis natural extracts.
Keywords: green tea